A Selenenium-Bridged 10-Boratriptycene Lewis Acid - Osi, Arnaud; Tumanov, Nikolay; Wouters, Johan; Chardon, Aurélien; Berionni, Guillaume (Synthesis, 2022)
A non-planar triarylborane and a new member of the boratriptycene family bearing a selenium atom in bridgehead position of triptycene scaffold was generated and isolated as a boron-‘ate’ complex paired with a weakly coordinating anion. With similar electronegativity while possessing longer atom radius with respect to sulfur, the introduction a selenium atom, in the form of a selenenium moiety, at the bridgehead of a triptycene scaffold allows a very precise modification of the pyramidalization of the boron atom environment. Experimental and computational evaluation of the Lewis acidity of this new boratriptycene derivative gave qualitative information on how a modification of the pyramidalization of the boron environment affects alone Lewis acidity parameters of such pyramidal triarylborane.
Keywords: Lewis acids; main-group chemistry; organoboron compounds; triptycene; acidity scale